The Nature of an Ideal Society According to the Al-Quran Perspective - Wildan Solihin; Maspuroh; Fikri Abdillah Azam; N.Ulfi Alawiah; Alifya Nur Hafshah (Tilawah: Journal of Al-Qur'an Studies, 2025)
This journal examines the concept of society from the perspective of Islamic educational philosophy. This research aims to understand the Islamic view of the nature of society and the role of education in forming an ideal society. Through a literature study of classical Islamic sources and educational philosophy literature, this research found that Islam views society as an organic unity consisting of individuals who are interconnected and have common goals. Education in Islam has a central role in shaping the character of individuals and society, so as to create a just, prosperous and god-fearing society.